OPTIMASALISASI PENAGIHAN PELAYANAN JASA PENERBANGAN TERBANG LINTAS - Euis Saribanon; Sela Sela (Institut Transportasi dan Logistik Trisakti, 2014)
Which one of the service is the overflying billing services (Flying Cross Flight Services) to any airlines thta fly over the western part of Indonesia. The aim of this study is to enhance the service and the billing of the Flying Cross Flight Services. The researchers use SWOT as the analysis method to solve the billing problems. It describes the billing process of PJP Overflying, identifies any factors which caused ineffective billing process and of course analyses the internal and external factor to create a new strategy. This new strategy is expected to control the billing problems that already happened and to increase the effectiveness of the billing process and services of PJP Overflying in the future.